2012
DOI: 10.1039/c2jm31232h
|View full text |Cite
|
Sign up to set email alerts
|

High-performance indium phosphide nanowires synthesized on amorphous substrates: from formation mechanism to optical and electrical transport measurements

Abstract: InP NWs have been extensively explored for next-generation electronic and optoelectronic devices due to their excellent carrier mobility, exciton lifetime and wave-guiding characteristics. Typically, those NWs are grown epitaxially on crystalline substrates which could limit their potential applications requiring high growth yield to be printable or transferable on amorphous and flexible substrates. Here, utilizing Au as catalytic seeds, we successfully demonstrate the synthesis of crystalline, stoichiometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…Compared with previous results , the two bands show a blue‐shift of ∼152 and 74 nm, respectively. The significant blue shift in the detected spectrum is an expected result of quantum confinement effect , since both the diameters of the InP trunk (∼19 nm) and InP QDs (3–10 nm) in the spheres are comparable with the Bohr radius of bulk InP (∼20 nm), as previously discussed. The very broad emission linewidth can be attributed to the broad size distribution of the QDs , as indicated in Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Compared with previous results , the two bands show a blue‐shift of ∼152 and 74 nm, respectively. The significant blue shift in the detected spectrum is an expected result of quantum confinement effect , since both the diameters of the InP trunk (∼19 nm) and InP QDs (3–10 nm) in the spheres are comparable with the Bohr radius of bulk InP (∼20 nm), as previously discussed. The very broad emission linewidth can be attributed to the broad size distribution of the QDs , as indicated in Fig.…”
Section: Resultssupporting
confidence: 75%
“…Up to date, InP nanowires have been synthesized by various methods, such as metal organic vapor phase epitaxy , laser catalytic growth , molecular beam epitaxy , and metalorganic chemical vapor deposition (MOCVD) . However, very few papers in the literature were reported on the growth of single‐crystalline InP nanowires by CVD route, which is much simpler and economical in comparison to the other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Hui et al [36] reported a facile method for the synthesis of high-density InP NWs on the amorphous substrate using gold nanoclusters as catalyst. NWs were grown via VLS-chemical vapour deposition.…”
Section: Synthesis Of Indium Phosphide Nanowiresmentioning
confidence: 99%
“…More importantly, the smooth surface and the low twin-defect density do not scatter or trap electrons which is beneficial to the carrier transfer along NWs [18, 19]. Twin defects and a rough surface in InGaAs NWs can scatter and trap carriers which gives rise to a serious decline in the electrical performance of NWs [3, 4, 15]. Therefore, it is important to synthesize InGaAs NWs with controllable defect densities and a smooth surface to improve their electrical properties for various technological applications.
Fig.
…”
Section: Resultsmentioning
confidence: 99%